INTRODUCING CRYSTALLIZATION BACKWARD SUCTION TRAPPING LIPIDS AND DEBRIS AS PROPOSED ADDITIONAL FACTOR IN THE GENESIS OF CORONARY ARTERY DISEASE - Embi, Abraham A. (International Journal of Research -GRANTHAALAYAH, 2020)
Coronary artery disease progression involves a slow process of abnormal accumulation of lipid deposits to the inner walls of the arteries followed by an immune system response. It is known that an increase in lipid concentration could trigger cholesterol crystals deposition, thus starting a vicious cycle that could also progress into intra-arterial plaque formation, the hallmark of mature atheromas. The purpose of this manuscript is to introduce a proposed mechanism for the genesis of coronary artery disease; whereby the actual act of lipids crystallization starts a cycle demonstrated to induce additional crystallization via dehydration. Experiments demonstrate for the first time via images and video-recordings showing that when the onset crystallization occurs near the tissue (≅ 1 mm) a dehydration triggered backward hydrodynamic suction or vacuum ensues with enough force to withdraw lipid molecules from human tissue; these molecules are shown to adhere to the crystals.